A leitura dialógica na EJA : contribuições de Bakhtin para a Tertúlia Literária Dialógica - Cavequia, Sabrina Maria de Amorim (Universidade Federal de São Carlos, 2016)
Our objectives for this work are: 1) demonstrate, from Mikhail Bakhtin's theory, how an educational activity that promotes dialogic reading provides critical formation coordinated between orality and writing, the author authorship and the readers authorship in shared reading and 2) evidence how the reading of world and reading of word are given at the same time in an educational activity of success, such as Dialogic Literary Gatherings. It is a qualitative research and procedures are: a) participation in Dialogic Literary Gatherings; b) interviews about important moments in the life of the research subjects and with the teacher who performs the Dialogic Literary Gatherings in their classes; c) identification of meanings that emerge from the meeting between word and ideologies that are present during the reading. So as to do that, our references were the studies of Mikhail Bakhtin to compare and analyze the data, we discuss a new conception of reading, we reflect on the needs of the subjects of Youth and Adult Education (YAE) in school context and present the Dialogic Literary Gatherings as an educational activity of success that provides knowledge of quality to all participants involved through dialogic learning. As a result, we show the potential of the dialogic reading for the production of knowledge, for the constitution of innovative ways to mean text, more connected to the reality of the reader, we emphasize the need to discuss the educational practices of success that happen in YAE and reveal as the reader expands its own understanding of the world when it expands your reading comprehension.
Keywords: Dialogic Reading; Bakhtin; Ideology; Dialogic Literary Gatherings; Youth and Adult Education; Leitura dialógica; Bakhtin; Ideologia; Tertúlia Literária Dialógica; Educação de jovens e adultos; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM